Relationship the Fuzzy P-Ideal with Some Fuzzy Subset of BH-Algebra - Abdulaali Neamah, Suad; ., . (International Journal of Engineering and Technology, 2018)
ThisÂ workÂ involvedÂ someÂ studying ,we study and prove some theorems and a propositions which determine the relationships among the notion ofÂ fuzzy p-ideal with the intersection, union, image of function, inverse functionÂ and with some other fuzzy subsets of BH-algebra, also we gave some properties of this ideal of a BH-algebra.Â Â